# |
ODE |
Mathematica |
Maple |
\[
{}y^{\left (5\right )}+4 y^{\prime \prime \prime \prime }+5 y^{\prime \prime \prime }-6 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+2 y^{\prime \prime }-y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-2 y^{\prime \prime }+2 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (5\right )} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime \prime }-3 y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = 3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime } = \left (x -1\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+7 y^{\prime } = {\mathrm e}^{-7 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+16 y = \left (1-x \right ) {\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+25 y = {\mathrm e}^{5 x}
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-3 y^{\prime } = x \,{\mathrm e}^{\frac {3 x}{4}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime } = x \,{\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+25 y = \cos \left (5 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )-\cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = \sin \left (4 x +\alpha \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+8 y = {\mathrm e}^{2 x} \left (\sin \left (2 x \right )+\cos \left (2 x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+8 y = {\mathrm e}^{2 x} \left (\sin \left (2 x \right )-\cos \left (2 x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+13 y = {\mathrm e}^{-3 x} \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+k^{2} y = k \sin \left (k x +\alpha \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+k^{2} y = k
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+6 y^{\prime \prime }+11 y^{\prime }+6 y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime } = 3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y^{\prime } = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y^{\prime \prime } = 3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-y^{\prime \prime \prime } = 4
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+4 y^{\prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+y^{\prime \prime } = {\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+y^{\prime \prime } = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+y^{\prime \prime } = x \,{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime }+4 y = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime }+4 y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime }+4 y = \sin \left (2 x \right ) x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 n^{2} y^{\prime \prime }+n^{4} y = a \sin \left (n x +\alpha \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 n^{2} y^{\prime \prime }+n^{4} y = \cos \left (n x +\alpha \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+6 y^{\prime \prime }+4 y^{\prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+6 y^{\prime \prime }-4 y^{\prime }+y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+6 y^{\prime \prime }-4 y^{\prime }+y = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = -2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime } = -2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 9
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime } = 1
\] |
✓ |
✓ |
|
\[
{}5 y^{\prime \prime \prime }-7 y^{\prime \prime } = 3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-6 y^{\prime \prime \prime } = -6
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime \prime \prime }+y^{\prime \prime \prime } = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+2 y^{\prime \prime }-2 y^{\prime }+y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y^{\prime } = 8 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 k y^{\prime }+k^{2} y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 8 \,{\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+3 y = 9 \,{\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}7 y^{\prime \prime }-y^{\prime } = 14 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = 3 x \,{\mathrm e}^{-3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+5 y^{\prime }+6 y = 10 \left (1-x \right ) {\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+2 y = 1+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = \left (x^{2}+x \right ) {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }-2 y = 8 \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 4 x \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 m y^{\prime }+m^{2} y = \sin \left (n x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = {\mathrm e}^{-x} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+a^{2} y = 2 \cos \left (m x \right )+3 \sin \left (m x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime } = {\mathrm e}^{x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime } = 4 \left (\cos \left (x \right )+\sin \left (x \right )\right ) {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+5 y = 10 \,{\mathrm e}^{-2 x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+8 y^{\prime } = x \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = x^{2} {\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = \left (x^{2}+x \right ) {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = x^{2}+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+2 y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime } = x^{2}+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = x^{2} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = x^{2} {\mathrm e}^{-x} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-2 y^{\prime \prime }+y = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = {\mathrm e}^{x} \cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+5 y = {\mathrm e}^{2 x} \left (\sin \left (x \right )+2 \cos \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{x}+{\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime } = x +{\mathrm e}^{-4 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = x +\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+2 y = \left (\sin \left (x \right )+1\right ) {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime } = 1+{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+4 y^{\prime } = {\mathrm e}^{2 x}+\sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \sin \left (x \right ) \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime } = 2 \cos \left (4 x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = 4 x -2 \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime } = 18 x -10 \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 2+{\mathrm e}^{x} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+2 y = \left (5 x +4\right ) {\mathrm e}^{x}+{\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 4 \,{\mathrm e}^{-x}+17 \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }-3 y^{\prime }-2 y = 5 \,{\mathrm e}^{x} \cosh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = x \sin \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+2 y^{\prime \prime }+2 y^{\prime }+y = x \,{\mathrm e}^{x}+\frac {\cos \left (x \right )}{2}
\] |
✓ |
✓ |
|